2021
DOI: 10.1161/atvbaha.120.315703
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Regenerative Capacity and the Obesity Paradox in Coronary Artery Disease

Abstract: Objective: The underlying pathobiology of the paradoxical relationship between obesity and outcomes in coronary artery disease (CAD) is unclear. Our objective was to determine the association between obesity and circulating progenitor cell (CPC) counts—a measure of intrinsic regenerative capacity—in asymptomatic individuals and patients with CAD and its impact on the obesity paradox. Approach and Results: CPCs were enumerated by flow cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 47 publications
0
12
0
1
Order By: Relevance
“…But interestingly, through big data analysis, it can be found that there is no nonlinear relationship between the degree of obesity and atherosclerosis. Studies have shown that when CPC is used as an index of endogenous vascular proliferation to study this paradox, the number of good outcomes of high regenerative capacity (i.e., high CPC count) in obese people is more [ 80 ]. On the other hand, the degree of visceral obesity and BMI index is not linear [ 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…But interestingly, through big data analysis, it can be found that there is no nonlinear relationship between the degree of obesity and atherosclerosis. Studies have shown that when CPC is used as an index of endogenous vascular proliferation to study this paradox, the number of good outcomes of high regenerative capacity (i.e., high CPC count) in obese people is more [ 80 ]. On the other hand, the degree of visceral obesity and BMI index is not linear [ 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other potential mechanisms include lower activation of the sympathetic nervous system ( 43 ) and higher circulating progenitor cell (CPC) counts ( 44 ) in obesity patients. It has been proved that persisting activation of the sympathetic nervous system will lead to poor prognosis of HF ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…CPCs are mononuclear cells that related to an endogenous regenerative or reparative system, contributing to vascular repair as well as regeneration ( 47 ). While obesity was independently associated with higher CPC counts, which may indicate a better prognosis ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increased muscle strength in obesity has also been associated with a better prognosis [ 12 ].In this evaluation of the obesity paradox, BMI is a protective factor in both lower and higher CRP groups [ 23 ]. In obese people with CAD, endogenous regenerative capacity can be measured by using cell progenitor counts, which also explains this obesity paradox [ 6 ]. The relation of obesity with adverse outcomes in CAD is indirectly proportional to those with a preserved endogenous regenerative capacity which is higher cell progenitor cell counts [ 6 ].…”
Section: Reviewmentioning
confidence: 99%
“…The risks of developing CAD increased by 40% with every 10 cm rise in waist circumference, with an odds ratio of 1.04 (95% CI: 1.01-1.07, P = 0.013) for a 1 cm increment [ 4 ]. The obesity paradox has been seen in some patient populations, but the pathophysiologic mechanisms causing it are not fully understood [ 6 ]. Metabolically healthy obesity (MHO) is one type of obesity without any cardiometabolic risk factors such as hypertension, dyslipidemia, insulin resistance, and type 2 diabetes mellitus [ 7 ].…”
Section: Introductionmentioning
confidence: 99%